Proceedings of the International Conference on Modeling Analysis and Simulation of Wireless and Mobile Systems on International 2022
DOI: 10.1145/3551659.3559059
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptable Module for Designing Jamming Attacks in WiFi Networks for ns-3

Abstract: The inherent openness of wireless communication techniques has made them vulnerable to jamming attacks. However, the effectiveness of a jamming attack depends on numerous parameters and varies according to the state of the environment. At the same time, attacks are becoming increasingly sophisticated and attempt to evade basic detection methods. Consequently, there is a real need to evaluate this new type of attack to improve the robustness of the detection and mitigation methods. A simulating tool to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Characteristics/Features Limitations [26] Reactive Jamming Frequency hopping, random time intervals Limited effectiveness [30] Continuous Wave Jamming Continuous interference signal, signal strength modulation Continuous interference signal hinders detection [31] Reactive Jamming Dynamic power levels, spread spectrum modulation Real-time detection challenges [32] Sweep Jamming Wideband jamming, frequency agility Sweep jamming across frequencies is hard to detect.…”
Section: Ref Attackmentioning
confidence: 99%
“…Characteristics/Features Limitations [26] Reactive Jamming Frequency hopping, random time intervals Limited effectiveness [30] Continuous Wave Jamming Continuous interference signal, signal strength modulation Continuous interference signal hinders detection [31] Reactive Jamming Dynamic power levels, spread spectrum modulation Real-time detection challenges [32] Sweep Jamming Wideband jamming, frequency agility Sweep jamming across frequencies is hard to detect.…”
Section: Ref Attackmentioning
confidence: 99%
“…The result showed that during mitigation, PDR was 0% and during mitigation, it varies between 60% and 70%. A k-tuple Full Withholding (KTFW) algorithm was proposed for CSMA/CA in [18] to increase the resilience of MAC against jamming attacks. The algorithm is meant for an environment where nodes are not allowed to add extra information to the packet and the nodes are listening for feedback on the channel continuously.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, a number of defenses have been put out to counteract jamming attempts, including the use of jamming-resistant protocols and the incorporation of anti-jamming algorithms into wireless devices. A jammer attack module is suggested by Bout et al [8] utilizing Network Simulator-3 (NS-3). This platform create an intelligent channel hopping mechanism and a jamming attack based on prior efforts to show its scalability.…”
Section: Literature Reviewmentioning
confidence: 99%